2011
DOI: 10.4187/respcare.01067
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Slow Expiration Technique in Infants: Effects on Tidal Volume, Peak Expiratory Flow, and Expiratory Reserve Volume

Abstract: BACKGROUND: Prolonged slow expiration (PSE) is a physiotherapy technique often applied in infants to reduce pulmonary obstruction and clear secretions, but there have been few studies of PSE's effects on the respiratory system. OBJECTIVE: To describe PSE's effects on respiratory mechanics in infants. METHODS: We conducted a cross-sectional study with 18 infants who had histories of recurrent wheezing. The infants were sedated for lung-function testing, which was followed by PSE. The PSE consisted of 3 sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 31 publications
1
25
0
8
Order By: Relevance
“…PSE is applied during the late phase of expiration up to the residual volume to improve interaction of the expiratory airflow with the mucus layer (23)(24)(25), specifically within the distal, narrower airways. The rational for its use is based on the evidence that airflows highly interact with mucus when the airways are narrower (7).…”
Section: Discussionmentioning
confidence: 99%
“…PSE is applied during the late phase of expiration up to the residual volume to improve interaction of the expiratory airflow with the mucus layer (23)(24)(25), specifically within the distal, narrower airways. The rational for its use is based on the evidence that airflows highly interact with mucus when the airways are narrower (7).…”
Section: Discussionmentioning
confidence: 99%
“…The actual physical therapy techniques are showed short-term benefits with PSE to some respiratory symptoms of bronchial obstruction in infants with AVB. The impact of this specific technique, in addition to the deflation of ERV is the increase in tidal volume resulting from subsequent activation of the Hering-Breuer reflex by a prolonged expiratory time and sighs [33][34][35] , which, in the infant, is clinically important because the inherent differences between the infant and adult making the respiratory system more likely to develop muscle fatigue and discomfort. Bernard-Narbonne et al 11 showed an increase in tidal volume and SpO 2 in the CP group of infants with AVB mechanical ventilation using slow expiratory flow as their technique of choice.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in lung volume is associated with the protective reflex of the airways, which restores lung volume by sigh breathing (Hering-Breuer deflation reflex). 52 As secretions reach the proximal airways, provoked cough takes over.…”
Section: Chest Physical Therapymentioning
confidence: 99%